ESP MATERIALS EVALUATION: INFORMATICS STUDENTS’ PERSPECTIVES - Viar Dwi Kartika; Yuni Awalaturrohmah Solihah (IAIN Syekh Nurjati Cirebon, 2023)
This present study investigated the students’ perspectives on ESP materials for the Informatics students. Qualitative research using 15 questionnaires to collect the data from 50 students of Informatics in the third semester of Universitas Catur Insan Cendekia. The findings showed that there had a positive perspective from the students to evaluate the ESP materials that were implemented for one semester. The ESP materials evaluation involves four main points. Firstly, the ESP materials are helpful and interesting. Then, ESP materials make the students more confident to learn independently. ESP materials develop the students’ critical thinking skills. Lastly, the ESP materials are presented attractively. This present study suggests the ESP teachers/practitioners to develop ESP materials to be applied in the ESP classroom.